The role of clothing on participation of persons with a physical disability: A scoping review. (May 2020) - Esmail, Alida; Poncet, Frédérique; Auger, Claudine; Rochette, Annie; Dahan-Oliel, Noémi; Labbé, Delphine; Kehayia, Eva; Billebaud, Christophe; de Guise, Élaine; Lessard, Isabelle; Ducharme, Isabelle; Vermeersch, Olivier; et al.
Abstract: Determining ways to facilitate participation of persons with a physical disability is crucial and clothing may play a central role. This review aims to synthesize and examine the role of clothing on participation of persons with a physical disability. Six research databases and grey literature were searched following Arksey & O'Malley's six steps, including multiple expert consultations. English and French articles contributing to how clothing affects participation were included and tabulated based on the International Classification of Functioning, Disability and Health. Fifty-seven articles and 88 websites were included. A variety of stakeholder perspectives, diagnoses, and types of clothing were represented. Clothing mostly influences mobility and self-care, as well as various personal factors. Forty-nine percent of articles reported essential clothing design features to consider. Clothing is an important and complex environmental factor that interacts with all health domains, including participation. Future research should consider intersectoral initiatives. Highlights: This is the first review on the topic that includes scientific and grey literature. Clothing is an Environmental Factor that interacts with other health domains. Many articles focused on Mobility, and Self-Care related activities. Forty-nine percent of included articles report essential clothing design features. There seems to be sufficient information to design appropriate clothing.